Epitaxial-like Growth of Solution-processed PbZr0.4Ti0.6O3 Thin Film on Single-crystal Nb-doped SrTiO3 Substrate - Quoc, Trinh Bui Nguyen; Ha, Hoang (VNU Journal of Science: Mathematics - Physics; Vol 33 No 4, 2017)
PbZr 0.4 Ti 0.6 O 3 (PZT) thin films have been conventionally fabricated on traditional silicon substrates with a platinum bottom electrode; however, as a consequence of unit cell mismatch, the films are difficult to form as an epitaxial-like growth. Hence, PZT films deposited on single-crystal niobium doped SrTiO 3 (111) substrates (Nb:STO) are promising to solve this issue thanks to the similar perovskite structure between PZT and STO. Essentially, Nb:STO material is a conductor, playing a part in both bottom electrode and epitaxial substrate. In this work, 200-nm-thick PZT films were successfully fabricated on Nb:STO substrates by a solution process. One obtained that PZT(111) peak started to appear on the Nb:STO substrate at a low annealing temperature of 450 o C. Also, scanning electron microscopy observation shows smooth and homogeneous surface of PZT films on Nb:STO substrate with no grain boundary, which evidences for epitaxial-like growth of PZT thin films. Remnant polarization of 6 µ C/cm 2 and leakage current of 8×10 -8 A were obtained at applied voltage of 5 V.